(untitled) (Chimica nella Scuola, 2023)
Usually, at the level of basic chemistry in the first two years of secondary school, the reaction rate is defined by referring to the average speed; sometimes and only briefly the concept of instantaneous speed is mentioned. In this article a possible in-depth analysis of the instantaneous reaction rate is provided; the analysis is not based on a theoretical-descriptive way, but uses an experimental-inductive approach.